Treatment of acute pain in cats - White, Kate L. (Wiley, 2017)
The cat's popularity as a pet continues to grow, with the most recent surveys showing approximately 17% of the population live with cats. This increased popularity of cats invariably means that more cats are presented to veterinary surgeons for surgery and treatment of painful conditions, but it seems that the treatment of pain in the cat has lagged behind that of other species. Lack of analgesic administration may well stem from the difficulties in assessing pain in the cat, but is probably compounded by the false perceptions of the likelihood of severe side effects occurring more frequently with the use of opioids and non-steroidal anti-inflammatory drugs in cats, thereby inadvertently denying them the analgesics they require. This article complements a previous article covering the assessment of acute pain in the cat (White, 2016); the aim of this second article is to provide an evidence-based framework to follow for the treatment of acute pain in the cat.